Imperfect Choice or Imperfect Attention? Understanding Strategic Thinking in Private Information Games - Brocas, I.; Carrillo, J. D.; Wang, S. W.; Camerer, C. F. (Review of Economic Studies, 2014)
To understand the thinking process in private information games, we use “Mousetracking” to record which payoffs subjects attend to. The games have three information states and vary in strategic complexity. Subjects consistently deviate from Nash equilibrium choices and often fail to look at payoffs which they need to in order to compute an equilibrium response. Choices and lookups are similar when stakes are higher. When cluster analysis is used to group subjects according to lookup patterns and choices, three clusters appear to correspond approximately to level-3, level-2, and level-1 thinking in level-k models, and a fourth cluster is consistent with inferential mistakes (as, for example, in QRE or Cursed Equilibrium theories). Deviations from Nash play are associated with failure to look at the necessary payoffs. The time durations of looking at key payoffs can predict choices, to some extent, at the individual level and at the trial-by-trial level.